Numerical Algorithm for the Third-Order Partial Differential Equation with Three-Point Boundary Value Problem - Jing Niu; Ping Li (Abstract and Applied Analysis)
A numerical method based on the reproducing kernel theorem is presented for the numerical solution of a three-point boundary value problem with an integral condition. Using the reproducing property and the existence of orthogonal basis in a new reproducing kernel Hilbert space, we obtain a representation of exact solution in series form and its approximate solution by truncating the series. Moreover, the uniform convergency is proved and the effectiveness of the proposed method is illustrated with some examples.